The Plant Cynomorium in Maltese Materia Medica - Charles Savona-Ventura (Wolters Kluwer Health/LWW, 2020)
The search for possible effective local therapeutic agents led to the discovery of a plant that was later known as Fungus Melitensis. This parasitic flowering plant was initially believed to grow only on a small islet off Gozo known variably as General's or Fungus Rock. It is now known to be more widely distributed with a range extending from the Canary Islands to China. First mentioned in 1647 by the Maltese historian Gian Francesco Abela, the plant was later described and illustrated in 1674 by the Palermo botanist Paolo Boccone, while a detailed clinical treatise was prepared in 1689 by the Maltese physician Gio Francesco Bonamico. Based on the principles of the "doctrine of signatures," the plant was considered useful by virtue of its color in conditions involving bleeding, while on the basis of the phallic appearance, it was considered efficacious for venereal disease. The medicinal properties of the plant became renowned throughout the European continent, increasing the demand for its collection and export. Measures were introduced to limit the collection to authorized individuals while physical access to the islet was made more difficult by cutting away the sloping parts of the islet. The plant lost its medicinal reputation during the early decades of the 19th century and has now been relegated to the annals of medical history and folklore, though it is still designated a protected species.